Smart cities, green technologies, and intelligent transport systems : 6th International Conference, SMARTGREENS 2017, and third International Conference, VEHITS 2017, Porto, Portugal, April 22-24, 2017, Revised selected papers /: 6th International Conference, SMARTGREENS 2017, and third International Conference, VEHITS 2017, Porto, Portugal, April 22-24, 2017, Revised selected papers. ([2019]) - Unknown
No abstract available